2019
DOI: 10.1108/jiabr-02-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity in the UAE Islamic banks

Abstract: Purpose The purpose of this study is to investigate the main factors that affect liquidity risk in the UAE Islamic banks. Design/methodology/approach The study examines the annual data of the seven UAE Islamic banks over the period 2008-2014. Random effects panel data model is used to estimate the impact of four bank-specific variables and two macroeconomic ones on the liquidity risk of the UAE Islamic banks via their impact on five alternative liquidity ratios. Findings The paper finds that bank size has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…This evidence is in conformity with the conclusion of Akhtar et al (2011) and Shamas et al (2018). This is, however, different from other studies that reached a positive statistically significant relationship (Ahmed et al, 2011;Iqbal, 2012) or negative and statistically significant link (Ghenimi and Omri, 2015;Alzoubi, 2017;Elbadry, 2018;ElMassah et al, 2019) between bank size and liquidity risk. This can be explained by the fact that GCC Islamic banks tend to keep a surplus of liquidity regardless of their size.…”
Section: Estimation Results and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This evidence is in conformity with the conclusion of Akhtar et al (2011) and Shamas et al (2018). This is, however, different from other studies that reached a positive statistically significant relationship (Ahmed et al, 2011;Iqbal, 2012) or negative and statistically significant link (Ghenimi and Omri, 2015;Alzoubi, 2017;Elbadry, 2018;ElMassah et al, 2019) between bank size and liquidity risk. This can be explained by the fact that GCC Islamic banks tend to keep a surplus of liquidity regardless of their size.…”
Section: Estimation Results and Discussionsupporting
confidence: 84%
“…For the macroeconomic variable, we found that GDP real growth rate has a positive but insignificant association with Islamic bank liquidity in GCC countries. In the same vein, ElMassah et al (2019) found an insignificant relationship between real GDP and three liquidity ratios for seven UAE Islamic banks during the period 2008-2014. This result is contrary to that of Rashid et al (2017), concluding that GDP growth is among the important determinants of bank's liquidity in Malaysia and GCC countries.…”
Section: Estimation Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Hasil penelitian ini sama dengan hasil penelitian (Hediati & Hasanuh, 2021), (Grilseda & Riyadi, 2021) dan (ElMassah et al, 2019) yang menyatakan CAR berpengaruh positif terhadap ROA. Hal ini menggambarkan bahwa semakin meningkat CAR akan meningkatkan ROA maka semakin tinggi kemampuan permodalan bank dalam menjaga timbulnya resiko kerugian yang mungkin terjadi, juga akan semakin banyak dana yang tersalurkan.…”
Section: Pembahasan Pengaruh Car Terhadap Profitabilitas (Roa)unclassified
“…The functioning of Mit Ghamr Local Savings Banks in Egypt from 1963 to 1967 is believed as a pioneering experiment of the current development of the Islamic banking industry worldwide (Maali and Napier 2010;Haniffa and Hudaib 2010;Hafsa Orhan Åström 2013;Jinjiri Ringim 2014;Alharbi 2017;Islam and Rahman 2017;Shome et al 2018;Lujja et al 2018;Mohammed et al 2019;Farooq 2019;ElMassah et al 2019;Pitchay et al 2019;Chamberlain et al 2020).…”
Section: Introductionmentioning
confidence: 99%